Factors that Influence Compensation Strategy from the Perspective of Personality and National Culture at Intel (Malaysia and Vietnam) - Chang, Pooi Wan (2010)
The main purpose of this study is to examine the relationships between individual personality and compensation package preferences at Intel Corporation and determine if cross-cultural differences exist in these preferences in Malaysia and Vietnam plants. A survey methodology was used and samples were taken from Intel employees in Malaysia and Vietnam. Data were collected from 110 employees by using simple random sampling. The study showed that there is relationship between Big Five personality and compensation package preferences but the value of each relationship are not strong in most cases. Nevertheless, cross-cultural differences do not exist in the employee's pay preference in Malaysia and Vietnam.